Ophthalmic Changes Following Maxillectomy With or Without Postoperative Radiation Therapy. Issue 5 (July 2019) - Sweeney, Adam R.; Walker, Brian; Bhrany, Amit D.; Chang, Shu-Hong; Jian-Amadi, Arash
Abstract : Purpose: To evaluate ophthalmic complications and quantitatively assess anatomic changes following maxillectomy with or without adjuvant radiotherapy in patients with midface malignancy. Methods: Twenty-four patients who underwent maxillectomy for sinus and/or paranasal cancer were included for retrospective review. Patients with complete ophthalmic examinations were evaluated for postoperative findings corresponding to sequelae of treatment. When available, anatomical changes including eyelid position were quantified from preoperative and postoperative full-face photos using computer software. Results: The most common complications identified in patients after maxillectomy were retraction/ectropion (50%), epiphora (29%), and exposure keratopathy/dry eye syndrome (25%). Patients treated with maxillectomy with adjuvant radiation therapy were more frequently found to have ophthalmic complications following treatment. In patients with available postoperative photos (n = 10), the mean ipsilateral margin reflex distance (MRD)2 and inferior scleral show were 8.4 mm and 2.4 mm, respectively. In patients with available preoperative photos (n = 5), the mean change in MRD2 and inferior scleral show following maxillectomy was 3.4 mm and 2.8 mm, respectively. Conclusion: Patients undergoing maxillectomy for the treatment of head and neck malignancy may be at significant risk for development of specific periocular complications. Lower eyelid malposition was the most significant postoperative quantitative eyelid change following maxillectomy, which may be exacerbated by adjuvant radiotherapy and inferior orbital rim removal. Abstract : Supplemental Digital Content is available in the text